DISAGREEMENT of Al IMAM Al KISAI (D: 189 A.H) to him SHEIKH Al-IMAM HAMZA(D: 156 A.H), and its IMPACT on the CRITICISM DIRECTED To Them - A COMPARATIVE Study - Hussein , Mohammed; Mosleh, Mohammed (Islamic Sciences Journal, 2023)
This research, entitled: [Disagreement of Al Imam Al Kisai (D: 189 A.H) to him Sheikh Al-Imam Hamza (D: 156 A.H), and its impact on the Criticism Directed to them - A comparative study], deals with a group of disagreement in Al Isoul Like Al Basmalah, Al Isteaza, Al Mad, Al Idgham and other Alhkam that are known by the specialist of this honored science, What does read by Al Imam Hamza and what does not read by Al Imam Al Kisai is considered disagreement whether Hamza approved by Al Jumhor or not and vice that versa showing the effect of the disagreement according to the clear criticism about the two readings . The researcher concluded many results, including: The difference in readings holy Quran is a variety difference and not controversial or opposite, Difference reading the Holy Quran is a followed Sunnah and wherever it is approved ensured people should take it in consideration, All the Isoul that criticized by critics reading of Al Imam Hamza doesn't belongs to him, It was shared by others like Al Shatiby, Al Dorrah, And Al Taiba..